The Integration of Artificial Intelligence in Supply Chain Management: A Comprehensive Review - Jubair, Hassan (ORGANIZE: Journal of Economics, Management and Finance, 2025)
This review explores the integration of artificial intelligence (AI) in supply chain management (SCM), providing a comprehensive overview of its applications across key functions such as procurement, production, inventory management, logistics, and customer service. AI technologies, including machine learning, predictive analytics, robotics, natural language processing, computer vision, blockchain, and the Internet of Things, are highlighted for their potential to enhance efficiency, reduce costs, and improve decision-making within supply chains. The paper also examines the challenges associated with AI adoption, including technical difficulties, data privacy concerns, and ethical considerations. Through a critical analysis of current literature and case studies, this review identifies key research gaps and suggests future directions for the development and implementation of AI in SCM. The findings underscore the transformative potential of AI while emphasizing the need for responsible adoption to address technical, organizational, and ethical issues.